A Critical Comparison of Correlations for Rapid Estimation of Subgrade Stiffness in Pavement Design and Construction - Christina Plati; Maria Tsakoumaki (Construction Materials, 2023)
According to pavement design principles, the subgrade or soil layer serving as the foundation for pavement depends on the properties and stiffness of the soil material. The resilient modulus (MR) is the absolute measure of the bearing capacity of the subgrade for pavement design. However, due to the complexity of MR testing, indirect methods are chosen to determine MR. In this context, the CBR test is considered a practical tool for determining the strength of the subgrade, but the use of the correlations of MR-CBR has caused great controversy in the scientific community. Nevertheless, such correlations are widely used in practice for pavement design, and the question of their influence on design results is always raised. Therefore, the present study investigates the use and applicability of the MR-CBR correlations for the subgrade with respect to the design of flexible pavements, with the aim of optimizing the thickness and bearing capacity of the unbound base/sub-base. Based on the previous debate on the use of MR-CBR correlations, this study first investigates the main correlations between MR and the CBR index based on a thorough review of the literature. Using the properties of certain medium-grained soils used in practice and the corresponding values of MR, estimated by the various MR-CBR correlations reported in the international literature, a theoretical pavement design is then carried out on the basis of a sensitivity analysis. A major outcome of the sensitivity analysis is the identification of the most optimal correlation for estimating MR in pavement design, while the development of a global MR-CBR correlation applicable to most types of soil materials used in pavement construction remains an important topic for future research.